Solution:
f(x) = \(x^3\) and g(x) = \(x^2\)
Now, fg(x) = f(\(x^2\)) [∵ g(x) = \(x^2\)]
= \((x^2)^3\)
= \(x^6\) is the required expression.
Questions
Quick Access
Exam Capsule
MCQ
Articles
Institutes
Notices
Top Topics
If f(x) = \(x^3 \) and g(x) = \(x^2\) find the expression for fg(x)
Solution:
f(x) = \(x^3\) and g(x) = \(x^2\)
Now, fg(x) = f(\(x^2\)) [∵ g(x) = \(x^2\)]
= \((x^2)^3\)
= \(x^6\) is the required expression.
PathshalaNepal.com is a Registered Company of E. Pathshala Pvt Ltd Nepal. Registration number : 289280
© 2020. All right Reversed.E. Pathshala Pvt Ltd